Improving the surface quality and mechanical properties of selective laser sintered PA2200 components by the vibratory surface finishing process - ŞİRİN, TOLGA; KAYNAK, YUSUF (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
This paper attempts to improve the physical and mechanical properties of selective laser sintered polyamide PA2200 components through a vibratory surface finishing process by inducing severe plastic deformation at the outer surface layers. The industrial target of additive manufacturing components is to obtain structures having surface roughness, hardness, and other mechanical properties equivalent to or better than those produced conventionally. Compared to the as-built SLS PA2200 samples, vibratory surface finishing treated specimens exhibited a smooth surface microstructure and more favorable roughness, hardness, and tensile strength. Also, the duration of the vibratory surface finishing process showed a further improvement in the surface roughness and hardness of the SLS samples. Compared to the as-built state, the roughness and hardness of the surface-treated samples improved by almost 90% and 15%, respectively. Consequently, microstructural analysis indicates that lower surface roughness and enhanced surface hardness is a crucial factor in influencing the overall tensile strength of SLS-PA2200 components. We consider that the combination of VSF and SLS processes can successfully handle a wide range of potential applications.This study also highlights the efficiency and applicability of the vibratory surface finishing process to other additive manufacturing processes and materials. [GRAPHICS] .
Keywords: Mechanical treatment; Selective laser sintering; Additive manufacturing; Surface roughness; Hardness; Mechanical strength